1975
DOI: 10.1055/s-0028-1097835
|View full text |Cite
|
Sign up to set email alerts
|

PHYTOCHEMICAL, PHARMACOLOGICAL, ANTIBACTERIAL AND ANTI–OVULATORY STUDIES ONANNONA SQUAMOSA

Abstract: Preliminary phytochemical, pharmacological, antibacterial and antiovulatory studies were conducted on the seeds of Annona squamosa, Linn. Qualitative analysis revealed the presence of alkaloids, reducing sugars, glycosides and steroids and the absence o f saponins, resins, tannins and volatile oils. Ethanofic extract exhibited no pharmacological, anti-bacterial or antiovtrlatory activities o f therapeutic significance.Annona squamosa Linn. (SHARIFA) is reputed to possess varied medicinal properties (KHAN, 1911… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 1 publication
0
18
1
Order By: Relevance
“…Although the fetus weight of some ANHMF exposed animals differed to control group, this parameter might vary with litter size. In contrast to that proposed by Vohora et al (1975) and Mishra et al (1979), our study demonstrates that plants from the Annonaceae family do not exhibit anti-ovulatory or abortive activity. These results indicate that ANHMF is safe to use during pre-pregnancy and/or throughout pregnancy.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Although the fetus weight of some ANHMF exposed animals differed to control group, this parameter might vary with litter size. In contrast to that proposed by Vohora et al (1975) and Mishra et al (1979), our study demonstrates that plants from the Annonaceae family do not exhibit anti-ovulatory or abortive activity. These results indicate that ANHMF is safe to use during pre-pregnancy and/or throughout pregnancy.…”
Section: Discussioncontrasting
confidence: 53%
“…However, herbal tea made from the leaves of Annona has been shown to induce a typical parkinsonism syndrome that is associated with the presence of acetogenins, such as annonacin (Champy et al, 2004). In addition, some studies have shown that different species of Annona, such as A. squamosa, cause anti-ovulatory and abortive activity in females (Vohora et al, 1975;Mishra et al, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…In traditional medicine, the leaves, seeds and fruits of this species are considered as antidiarrheal, antitumor, antimicrobial and anthelmintic remedies (Lorenzi andMatos 2002, Rieser et al 2004). Some phytochemical and pharmacological studies of A. squamosa seeds, including hypoglycemic, antiovulatory and insecticidal activities had been reported (Fouque 1972, Vohora et al 1975 . Rahman et al (2005) showed the antibacterial activity of four different extracts of A. squamosa seeds and Kotkar et al (2002) reported the antimicrobial activity of flavonoids isolated from the seeds.…”
Section: Introductionmentioning
confidence: 99%
“…This plant has recently come under intense scrutiny as potential source of the potent biologically active annonaceous acetogenins isolated from the seed and the bark [8]. Analysis of (A. squamosa) seed also reveals the presence of alkaloids [9], terpenoids [10] and saponins [11]. The leaf contains volatile oils.…”
Section: Introductionmentioning
confidence: 99%